(untitled) (Global Journal of Medical Research, 2016)
Background Recurrent hernias are still relatively common in our practice Despite the introduction of several therapeutic improvements recurrent hernias still appear in 10- 15 Therefore reasons for a recurrence are discussed in a more fundamental way It is assumed that a failure mainly depends on the quality of the repair Aim This study aimed to review and assesses the clinical presentation of recurrent hernia and predisposing factors to recurrent hernia deal with the therapeutic options for management of recurrent hernia and evaluate the postoperative complications Patients and methods Patients with incisional hernia and recurrent hernia referred for the surgical department at Khartoum Teaching Hospital during the period for 15 months were prospectively studied using a structured questionnaire Results Fifty patients were treated during study period M F ratio is 2 3 The age range was range between 21 to 80 years with mean age of 47 years The majority of cases were incisional hernia n 34 68 The index surgeries leading to the incisional hernia were caesarian section n 19 38 exploratory laparotomy n 13 26 The only significant factor associated with development of the incisional and recurrent hernia was physical activity such as heavy lifting n 34 68 P-value 0 011 Other factor like overweight multiple surgeries and when operator was a junior registrar were not significant Seroma formation was the most common postoperative complication seen in about n 47 94 of the patients Conclusion Incisional hernia is more common in lower segment caesarean sections and exploratory laparotomy Recurrent inguinal hernias are more common with heavy lifting and conventional non mesh repair P-value 005